2013
DOI: 10.4236/ajps.2013.45140
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Treatment of <i>Jatropha curcas</i> L. Leachates and Potassium on Growth and Phytochemical Constituents of Wheat (<i>Triticum aestivum</i> L.)

Abstract: Jatropha curcas L. commonly known as "physic nut" is an exotic species that shows invasive characters. Plantation of Jatropha species is being undertaken at a large scale for biodiesel production. The plants defoliate their leaves twice a year and have been shown to possess certain antinutritional factors. Seeds of Jatropha are removed from mature dried fruits for oil extraction and ovary walls are discarded. For the present experiments leachates from sun dried leaves and ovary walls of Jatropha curcas L. were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 29 publications
4
24
0
Order By: Relevance
“…Greater accumulation of phenolics in plants subjected to stressful conditions is ascribed to the upregulation of the enzymes involved in their synthesis (Wada et al 2014). In our study, increased phenols content in stressed plants corroborate with the findings of Mehr et al (2012) for A. graveolens L., Tomar and Agarwal (2013) for wheat and Dawood et al (2014) for Vicia faba. In confirmation with our results, Nell et al (2009) also observed increased phenols content in AMF-inoculated Salvia officinalis L. plants as compared to uninoculated counterparts.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Greater accumulation of phenolics in plants subjected to stressful conditions is ascribed to the upregulation of the enzymes involved in their synthesis (Wada et al 2014). In our study, increased phenols content in stressed plants corroborate with the findings of Mehr et al (2012) for A. graveolens L., Tomar and Agarwal (2013) for wheat and Dawood et al (2014) for Vicia faba. In confirmation with our results, Nell et al (2009) also observed increased phenols content in AMF-inoculated Salvia officinalis L. plants as compared to uninoculated counterparts.…”
Section: Discussionsupporting
confidence: 81%
“…Maintaining higher K/Na ratio is believed to be important strategy adopted by plants to mitigate stress-induced deleterious changes (Wu et al 2010;Azooz et al 2011;Tomar & Agarwal 2013). Optimal concentration of potassium is essential for several important metabolic processes (Tomar & Agarwal 2013;Ahmad et al 2014). Efficient compartmentation or exclusion of deleterious ions like Na contributes to maintenance of tissue osmotic potential so that hyper-osmotic effects can be averted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Filtrate was read directly on digital flame photometer using K, Na and Ca filters separately (Tomar & Agarwal 2013;Jatav et al 2014). …”
Section: Estimation Of K Na and Camentioning
confidence: 99%